Poisoned chalice : the last campaign of the Progressive Conservative Party? - McLaughlin, David, 1957- (Dundurn Press, 1994)
Poisoned Chalice chronicles the fateful end of the feredral Progressive Conservative government in Ottawa. In a day-by-day account of an election campaign seemingly doomed to disaster Poisoned Chalice covers the strategy, tactics and political machinations that drove the Condervative campaign from the point of view of someone on the bus.